1892 Miss. Laws 194, 198 - (:unkn) unknown (My University, 1892)
Ch. 74: Mandated tax assessors to have prepared rolls of taxable items, including guns(more than one), pistols, Bowie knives, dirks, and sword canes.
Keywords: TAX - PROPERTY OR SALES